P-60 Hospice-based ECHO™ tele-mentoring enables a community of practice for NHS neighbourhood team nurses. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Wilderspin, Nicola; Westwood, Debbie; Mistry, Rajesh; Ayris, Rachel; Curtis, Claire
Abstract : Background: During health sector reform, Worcestershire NHS community nurses were divided into 14 multi-professional 'neighbourhood' teams (NTs). Junior community nurses may be required to care for patients with complex palliative and end of life care needs as lone workers in remote settings, and NT managers recognised community nurse need for increased development and support. Aims: To test the feasibility of ECHO™ (Extension of Community Healthcare Outcomes) tele-mentoring to enhance the knowledge and skills of Band 5 community nurses to deliver palliative and end of life care in community settings, and to provide a vehicle for staff mentorship and support. Method: A Health Education England workforce development grant enabled an ECHO™ hub to be established at St Richard's Hospice, and a core team (three hospice staff and one NHS consultant) attended Hospice UK ECHO™ 'immersion training'. A fortnightly palliative and end of life care tele-mentoring network commenced in December 2018, delivering a curriculum set by 19 NHS band 5 community nurses selected from all NTs, at times selected by community nurses. Evaluation will include web-based questionnaires and focus group discussions. Outcomes: Sixteen community nurses from nine different NTs have attended the first nine ECHO™ sessions. Nursing engagement and feedback has been enthusiastic, and collaborative discussions have been facilitated across widely separated geographical teams. Case studies have demonstrated the complexity of the palliative care needs of patients on community nurse caseloads. Feedback from didactic teaching demonstrates the delivery of new knowledge. Community nurse workload made sustained individual attendance at each ECHO™ session challenging, so the same curriculum is being relaunched following discussions with NT managers. Conclusion: A hospice based ECHO™ hub can enable a supportive tele-mentoring network for community nurses who manage patients with complex palliative care needs in remote geographical locations. ECHO™ also provides an excellent opportunity for hospice-NHS partnership working to support the delivery of community palliative care services.